2019
DOI: 10.1111/cts.12702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genetic and Nongenetic Factors on the Clinical Response to Mineralocorticoid Receptor Antagonist Therapy in Egyptians with Heart Failure

Abstract: This prospective cohort study evaluated the association between the renin angiotensin aldosterone system genotypes and response to spironolactone in 155 Egyptian patients with heart failure with reduced ejection fraction (HFrEF). Genotype frequencies for AGT rs699 were: CC = 16%, CT = 48%, and TT = 36%. Frequencies for CYP11B2 rs1799998 were: TT = 33%, TC = 50%, and CC = 17%. After 6 months of spironolactone treatment, change in the left ventricular ejection fraction (LVEF) differed by AGT rs699 (CC, 14.6%; TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Our finding on the frequency of genetic polymorphisms in Egyptian pancreatic and NSCL cancer patients reported herein does not match that of Africans, Latin Americans, Asians, or Europeans ( Table S3 ). This supports previous reported data related to Egyptians and non-Egyptians ( 40 43 ). Indeed, previous studies also revealed such a discrepancy among Asian and non-Asian ethnicity regarding the TNF-308 G/A polymorphisms in hepatocellular carcinoma risk ( 12 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our finding on the frequency of genetic polymorphisms in Egyptian pancreatic and NSCL cancer patients reported herein does not match that of Africans, Latin Americans, Asians, or Europeans ( Table S3 ). This supports previous reported data related to Egyptians and non-Egyptians ( 40 43 ). Indeed, previous studies also revealed such a discrepancy among Asian and non-Asian ethnicity regarding the TNF-308 G/A polymorphisms in hepatocellular carcinoma risk ( 12 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our finding on the frequency of genetic polymorphisms in Egyptian pancreatic and NSCL cancer patients reported herein does not match that of Africans, Latin Americans, Asians, or Europeans (Table S3). This supports previous reported data related to Egyptians and non-Egyptians (40)(41)(42)(43). Indeed, previous studies also revealed such a discrepancy among Asian and non-Asian ethnicity regarding the TNF-308 G/A polymorphisms in hepatocellular carcinoma risk (12).…”
Section: Discussionsupporting
confidence: 91%
“…ARA utilization may be improved if clinicians could preemptively identify patients who are likely to benefit from ARA treatment, while sparing those not expected to benefit from ARA‐associated risks. With the recognition of HF as a phenotypically heterogeneous disease and with known variations in drug response, a personalized approach is a potential strategy to optimize spironolactone use and ultimately improve patient outcomes 16–19 …”
Section: Introductionmentioning
confidence: 99%
“…In vitro, the SNP rs1799998 (c.‐344T>C) results in a higher binding affinity of CYP11B2 to the inhibitory steroidogenic transcription factor 1 (SF‐1), 28 contributing to a decreased production of aldosterone 29 . Evidence suggests that these SNPs may be associated with spironolactone effectiveness in heart failure with reduced ejection fraction (HFrEF) patients 18,19 ; however, they have not been studied in an HFpEF population.…”
Section: Introductionmentioning
confidence: 99%